Exciton absorption spectra of KPb2Br5 thin films - Kovalenko, E. N.; Kovalenko, V. V.; Yunakova, O. N.; Yunakov, N. N. (Institute for Single Crystals, 2016)
The absorption spectrum of KPb2Br5 thin film of tetragonal (I) and monoclinic (II) structures were investigated in the spectral region of 2-6 eV and the temperature range 90-440K. It was found that KPb2Br5 (I) of the tetragonal structure irreversibly becomes in KPb2Br5(II) of the monoclinic structure when T = 293 K. It is found that low-frequency exciton excitations of KPb2Br5 (I, II) are localized in the sublattice, which contains ions Pb2+, and its are two-dimensional nature.
Keywords: thin films; absorption spectra; exitons; phase transition